Special Needs Administrator and emotional categories of solidarity - Paniccia, Rosa Maria (Quaderni di Psicologia Clinica, 2014)
The paper explores the legal institution of Special Needs Administrator (in Italian, amministratore di sostegno) in terms of social mandate, from both the interest in clinical psychological intervention with people at risk of social exclusion and an ongoing research study on this figure (introduced by the law n. 6 2004). It therefore deals with the constitutional value of solidarity as civic attitude opposed to organizational competence. Some clues suggest the organizational incompetence present in our culture and the experience of homo homini lupus in social relationships, so that the desired autonomy on the one hand refers to conformism and on the other hand to defense capability from enemies. In addition, intervention on relationships is not recognized while the only professional service that can be remunerated deals with the individual. The individualist and normalized “psychology” entailed by this solidarity, traced in legal language and consistent with the medical one, profoundly differs from that of our experience in research and intervention. The function of Special Needs Administrator, based on this culture, however, is affected by contradictions and conflicts. It therefore seems like a very interesting role to find ways in which psychology can usefully confront itself with medicalization and legal perspective, respecting differences and looking for integration.